The Right of Meskhetian Turks to Return to Their Country - Ceren Zeynep Pirim; Emre Öktem (Public and Private International Law Bulletin)
Meskhetian Turks were deported from the Meskhetian region of the Georgian Soviet Socialist Republic in November 1944, following the State Defence Committee of the Union of Soviet Socialist Republics’ decision No. 6279 (July 31, 1944). In 1989, just two years before the collapse of the Soviet Union, a significant number of Meskhetian Turks residing in Uzbekistan’s Fergana region were forcibly relocated by the Soviet administration to various parts of the Soviet Union, resulting in a second wave of deportation. Today, Meskhetian Turks live not only in the former Soviet territories but also in several States, notably Türkiye and the United States of America. This article explores the legal pathways that could enable Meskhetian Turks, now dispersed globally, to return to their ancestral homeland in the Meskhetian region of present-day Georgia. The first section focuses on the history of the Meskhetian Turks, detailing their deportation and subsequent efforts to return to their country. The second section examines the definition, scope, and nature of the ‘right of return,’ explores whether Meskhetian Turks possess this right under the law of state succession, and studies the legal remedies available to them. It is proposed that the Human Rights Committee, the supervisory body of the 1966 United Nations Covenant on Civil and Political Rights, would serve as the most effective mechanism for enabling Meskhetian Turks to reclaim their right to return to their homeland.